SCIENTIFIC AND PEDAGOGICAL REVIEWING: BIG PROBLEMS OF A SMALL GENRE - Alevtina S. Robotova (Высшее образование в России)
The paper addresses the problem of writing the modern scientific and pedagogical review. A reviewer faces a lot of questions concerning peer review process. The author considers the review as a genre influencing on the development of scientific and pedagogical knowledge.